Persistently expressed human chorionic gonadotropin induces premature luteinization and progressive alterations on the reproductive axis in female mice - Marcial Lopez, Agustina; Ratner, Laura D.; Martinez, Carolina S.; Di Giorgio, Noelia; Poutanen, Matti; Huhtaniemi, Ilpo T.; Rulli, Susana B. (General and comparative endocrinology, 2023)
•Elevated human chorionic gonadotropin hormone (hCG) induced female infertility.•A progressive impairment of the reproductive function occurred from peripuberty.•Persistently elevated levels of hCG induced prolactin synthesis and secretion.•Elevated hCG and prolactin induced premature luteinization of the ovary and progesterone synthesis.•Transgenic female mice overexpressing hCG became a suitable model to study hyperprolactinemia. The hypothalamic–pituitary–gonadal axis plays a fundamental role in the endocrine regulation of the reproductive function in mammals. Any change in the function of the participating hormones or their receptors can lead to alterations in sexual differentiation, the onset of puberty, infertility, cancer development, and other dysfunctions. In this study, we analyzed the influence of persistently elevated levels of the human chorionic gonadotropin hormone (hCG), a powerful agonist of pituitary luteinizing hormone (LH), on the reproductive axis of female mice. As a consequence of chronic hCG hypersecretion through a global expression of the hCGbeta-subunit in transgenic (TG) female mice, a series of events perturbed the prepubertal to juvenile transition. The imbalance in gonadotropin action was first manifested by precocious puberty and alterations in gonadal hormone production, with the consequent ovarian function disruption and infertility in adulthood. The expansion of cumulus cells in vivo and in vitro, ovulatory capacity, and gene expression of ovulation-related marker genes after hormone stimulation were normal in 3-week-old TG females. However, the expression of genes related to steroidogenesis and luteinization such as Lhcgr, Prlr, and the steroidogenic enzymes Cyp11a1, Cyp17a1, and Cyp19a1 were significantly elevated in the TG females. This study demonstrates that the excessive secretion of hCG in concert with high prolactin, induced premature luteinization, and enhanced ovarian steroidogenesis, as was shown by the up-regulation of luteal cell markers and progesterone synthesis in the TG mice. Furthermore, progressively impaired reproductive function of the TG females occurred from the peripubertal stage to adulthood, thus culminating in infertility.